Increased epithelial membrane protein 2 expression in glioblastoma after treatment with bevacizumab. Issue 1 (8th September 2020) - Patel, Kunal S; Kejriwal, Sameer; Thammachantha, Samasuk; Duong, Courtney; Murillo, Adrian; Gordon, Lynn K; Cloughesy, Timothy F; Liau, Linda; Yong, William; Yang, Isaac; Wadehra, Madhuri
Abstract: Background: Antiangiogenic therapy with bevacizumab has failed to provide substantial gains in overall survival. Epithelial membrane protein 2 (EMP2) is a cell surface protein that has been previously shown to be expressed in glioblastoma, correlate with poor survival, and regulate neoangiogenesis in cell lines. Thus, the relationship between bevacizumab and EMP2 was investigated. Methods: Tumor samples were obtained from 12 patients with newly diagnosed glioblastoma at 2 time points: (1) during the initial surgery and (2) during a subsequent surgery following disease recurrence post-bevacizumab treatment. Clinical characteristics and survival data from these patients were collected, and tumor samples were stained for EMP2 expression. The IVY Glioblastoma Atlas Project database was used to evaluate EMP2 expression levels in 270 samples by differing histological areas of the tumor. Results: Patients with high EMP2 staining at initial diagnosis had decreased progression-free and overall survival after bevacizumab ( median progression-free survival 4.6 months vs 5.9 months; log-rank P = .076 and overall survival 7.7 months vs 14.4 months; log-rank P = .011 ). There was increased EMP2 staining in samples obtained after bevacizumab treatment in both unpaired ( mean H-score 2.31 vs 1.76; P = .006 ) and paired analyses ( mean difference 0.571; P = .019 ). This expression increase correlated with length of bevacizumab therapy ( R 2   = 0.449; Pearson P = .024 ). Conclusions: Bevacizumab treatment increased EMP2 protein expression. This increase in EMP2 correlated with reduced mean survival time post-bevacizumab therapy. We hypothesize a role of EMP2 in clinical bevacizumab resistance and as a potential antiangiogenic therapeutic target in glioblastoma.